2022
DOI: 10.1038/s41419-022-05345-z
|View full text |Cite
|
Sign up to set email alerts
|

The oncoprotein MUC1 facilitates breast cancer progression by promoting Pink1-dependent mitophagy via ATAD3A destabilization

Abstract: Mitophagy is a vital process that controls mitochondria quality, dysregulation of which can promote cancer. Oncoprotein mucin 1 (MUC1) targets mitochondria to attenuate drug-induced apoptosis. However, little is known about whether and how MUC1 contributes to mitochondrial homeostasis in cancer cells. We identified a novel role of MUC1 in promoting mitophagy. Increased mitophagy is coupled with the translocation of MUC1 to mitochondria, where MUC1 interacts with and induces degradation of ATPase family AAA dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…ATAD3A knockdown promotes the growth of hepatocellular carcinoma xenograft tumors 18 . In breast cancer, ATAD3A was also found to act as a tumor suppressor gene, and overexpression of ATAD3A inhibited cancer cell proliferation and tumorigenesis 11 . However, other studies have reported that ATAD3A plays a pro‐oncogenic role in the development of tumors such as prostate cancer and head and neck cancer 8,19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ATAD3A knockdown promotes the growth of hepatocellular carcinoma xenograft tumors 18 . In breast cancer, ATAD3A was also found to act as a tumor suppressor gene, and overexpression of ATAD3A inhibited cancer cell proliferation and tumorigenesis 11 . However, other studies have reported that ATAD3A plays a pro‐oncogenic role in the development of tumors such as prostate cancer and head and neck cancer 8,19 .…”
Section: Discussionmentioning
confidence: 99%
“…This promotes proliferation and invasion of head and neck cancer cells 8 . ATAD3A not only plays an important role in the epithelial–mesenchymal transition of tumor cells, but also affects other biological processes, such as DNA repair and cell apoptosis in tumor cells, 9,10 ultimately influencing tumor cell growth and metastasis 11 . Furthermore, ATAD3A is also involved in the sensitivity and resistance of tumor drugs.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, mitochondria and breast cancer cells maintain a symbiotic relationship via multiple mechanisms that are intricately interconnected to each other to further promote breast cancer survival and growth ( Figure 2 ). Additional mitochondria-associated factors not discussed in this review, such as mitophagy and ROS-induced senescence [ 222 , 223 ], may also support breast cancer progression. Thus, targeting mitochondria is reasonable in breast cancers, and numerous drugs have been developed [ 224 , 225 ].…”
Section: Evidence That Mitochondria Are a Target In Breast Cancermentioning
confidence: 99%
“…Among prognosis study, a pan-cancer analysis demonstrated that low expressed MFN2 due to mitochondrial dysfunction was associated with poor prognosis of renal clear cell carcinoma [ 51 ]. In 321 breast cancer cases, patients with high expression of Pink1 had shorter overall survival [ 52 ]. Relevant mechanisms have been preliminarily explored.…”
Section: Roles Of Mitochondrial Dynamics In Maintaining Mitochondrial...mentioning
confidence: 99%